Instability of homogeneous composition of highly strained quantum wells in heterostructures GaAs/InxGa₁₋xAs/GaAs - Klimovskaya, A.I.; Grigor’ev, N.N.; Gule, E.G.; Dryha, Yu.A.; Litovchenko, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
InxGa₁-xAs QW-layers embedded in GaAs matrix have been characterized by photoluminescence (PL). The relation between the PL parameters and mismatch of the lattice parameters of the layer and matrix was established. In highly strained layers several PL bands were observed instead one band. This is probably a result of alternating content of In raised only in highly strained layers.